PENGARUH PROFITABILITAS, RISIKO BISNIS, UKURAN PERUSAHAAN, DAN PAJAK TERHADAP STRUKTUR MODAL - LAILATUS SA'ADAH; Mohamad Soedarman; Erina Priscilla Natalia (Universitas Riau Kepulauan, 2022)
The purpose of this study was to analyze the effect of profitability, business risk, firm size and tax on capital structure. The sample from this study used 19 companies from 65 property and real estate companies on the Indonesia Stock Exchange (IDX) for the 2018-2020 period which were taken using the purposive sampling method. Tests in the study used multiple linear regression techniques and for hypothesis testing, used the coefficient of determination (R2) and t-test. The results of this study identify that the variables of profitability, business risk, and firm size do not affect capital structure, while taxes have a significant and positive influence on capital structure.